Establishing the aims, format and function for multidisciplinary team-driven care within an inflammatory bowel disease service: a multicentre qualitative specialist-based consensus study. Issue 1 (10th August 2017) - Morar, Pritesh S; Sevdalis, Nick; Warusavitarne, Janindra; Hart, Ailsa; Green, James; Edwards, Cathryn; Faiz, Omar
Abstract : Objective: To obtain a specialist-based consensus on the aims, format and function for MDT-driven care within an inflammatory bowel disease (IBD) service. Design: This was a prospective, multicentre study using a Delphi formal consensus-building methodology. Setting: Participants were recruited nationally across 13 centres from July to August 2014. Participants: 24 participants were included into the Delphi Specialist Consensus Panel. They included six consultant colorectal surgeons, six gastroenterologists, five consultant radiologists, three consultant histopathologists and 4 IBD nurse specialists. Interventions: Panellists ranked items on a Likert scale (1=not important to 5=very important). Items with a median score >3 were considered eligible for inclusion. Main outcome measures: Consensus was defined with an IQR ≤1. Consensus on categorical responses was defined by an agreement of >60%. Results: A consensus on items (median; IQR) that described the aims of the MDT-driven care that were considered very important included: advance patient care (5;5-5), provide multidisciplinary input for the patient's care plan (5;5-5), provide shared experience and expertise (5;5-5), improve patient outcome (5;5-5), deliver the best possible care for the patient (5;5-5) and to obtain consensus on management for a patient with IBD (5;4-5). A consensus for being a core MDT member was demonstrated for colorectal surgeons (24/24), radiologists (24/24), gastroenterologists (24/24), nurse specialists (24/24), dieticians (14/23), histopathologists (21/23) and coordinators (21/24). Conclusions: This study has provided a consensus for proposed aims, overall design, format and function MDT-driven care within an IBD service. This can provide a focus for core members, and aid a contractual recognition to ensure attendance and proactive contribution.